Effectiveness Of The "Peer Teaching" Approach In Socializing Digital Security Practices And Digital Footprint Management To Students Of SMP 8 Satap - Fariani, Putri; Muslimin, Muslimin; Ramdhani, Lisda (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to analyze the effectiveness of the Peer Teaching approach in promoting digital security practices and digital footprint management among students at SMP 8 SATAP Dompu. The research employed a quasi-experimental method with a non-equivalent control group pretest–posttest design. The experimental group received the Peer Teaching intervention, while the control group participated in conventional dissemination through lectures and leaflets. Data were collected through knowledge tests, attitude and behavior questionnaires, classroom observations, and interviews. Data analysis involved paired-sample t-tests, independent t-tests, the Shapiro–Wilk normality test, and effect size analysis (Cohen’s d). The results showed that the Peer Teaching approach significantly increased digital security knowledge scores from 58.00 to 85.30, with a gain of 27.3%, compared to the control group, which improved by only 13.4%. The t-value (3.652; p < 0.01) and Cohen’s d of 1.12 (large effect size) confirmed the effectiveness of the method. In addition to cognitive improvements, there were observable behavioral changes, such as adjusting privacy settings, using two-factor authentication, and showing greater social awareness in digital contexts. Thus, the Peer Teaching approach proved effective in enhancing students’ literacy and practices related to digital security.